Red galls: the different stories of two gall types on the same host - Bomfim, Phabliny M. S.; Cardoso, João C. F.; Rezende, Uiara C.; Martini, Vitor C.; Oliveira, Denis C. (Plant biology (Stuttgart, Germany), 2019)
Several studies have suggested reasons why galls have conspicuous colours, but none of the ideas have been confirmed. However, what if the vibrant colours of some galls are explained simply by the effect of light exposure? This may lead to anthocyanin accumulation, functioning as a defence mechanism against the effects of high light. We studied the globoid galls induced by Cecidomyiidae (Diptera) on Qualea parviflora ( Vochysiaceae ), relating anthocyanin accumulation and chlorophyll fluorescence parameters to light incidence in abaxial and adaxial galls. We also tested if the anthocyanin accumulation patterns apply to another Cecidomyiidae‐induced gall morphotype (intralaminar) within the same plant. Adaxial galls are exposed to higher incident light, with more anthocyanin accumulation and therefore red coloration. In galls from angled leaves, the greater the angle of the leaf, the higher the difference between anthocyanins on the sun and shade sides of galls. Photosynthetic pigment concentrations did not differ between abaxial and adaxial galls. However, we found higher ( F m ′ − F ′)/ F m ′ and F v / F m in the abaxial galls. Conversely, NPQ and R fd were higher in adaxial galls. Finally, the pattern of anthocyanin accumulation was not found in the intralaminar gall. Anthocyanin accumulation in galls functions as a photoprotective strategy, maintaining tissue vitality in regions exposed to high light conditions. However, this mechanism may vary even among galls within the same host, indicating idiosyncrasy when it comes to coloration in galls. To date, this is the first study to demonstrate quantitatively why the galls of a specific species may be coloured: the variation in light regimes creates differential anthocyanin accumulation, influencing coloration.